The effectiveness of biofilter as a treatment for domestic wastewater - Muhammad, Iskandar (2010)
Water supports all forms of life and affects our health, lifestyle, and economic well being. Water is also a resource that has many uses, including recreational, transportation, hydroelectric power, domestic, industrial, and commercial uses. Although more than three quarters of the earth's surface is made up of water, only 2.8% of the Earth's water is available for human consumption. Water demand in Malaysia has shift to 60% increase from 9543 MLD in 1995 to 15285 WD in 2010. So, treatment of water is important for human needs and considered as a long term mission for sustainable earth. In the intention to reduce water pollution, treatment for domestic wastewater treatment is done such as biofiltration as one of the alternative. Biofilter is easy to operate, reliable, and a cost-saving system to be implemented. There are many biofilters in studies nowadays but mostly the system fails when been implemented at site although it shows effective results during pilot test. The purpose of this research is to further harness the potential and capability of biofiltration to be used at site to comply with standards of Environmental Quality Act, 1974. Domestic wastewater is produced from kitchens, bathrooms and laundries in residential homes and from various commercial and industrial sources. The location of this study which is cafeteria has effluent discharge that is polluted due to poor wastewater management. This leads to dirty water discharged into Sungai Belat. The biofiltration zone consists of activated carbon, high capacity soils and healthy microbes from mud ball. The parameter that is used is study is based on Environmental Quality Act 1974. The parameters are pH, electric conductivity, turbidity, dissolved oxygen, temperature, salinity, Ammoniacal-Nitrogen, biochemical oxygen demand, chemical oxygen demand, total dissolved solid, total suspended solid, total coliform, E.Coli, and oil & grease.